1995
DOI: 10.1128/jcm.33.7.1779-1783.1995
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of clonal relationships among isolates of Shigella sonnei by different molecular typing methods

Abstract: Shigella sonnei is a major cause of diarrheal disease in developed as well as in developing countries. Epidemiologic studies of this organism have been limited by the lack of a simple and effective method for comparing strains. In this study, we have compared different molecular typing methods, i.e., plasmid profile analysis, restriction endonuclease analysis of plasmids, rRNA gene restriction analysis (ribotyping), pulsedfield gel electrophoresis (PFGE), and enterobacterial repetitive intergenic consensus (ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
4

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(41 citation statements)
references
References 24 publications
1
36
0
4
Order By: Relevance
“…The present study showed the poor discriminatory power of ribotyping for S. sonnei isolates. This ®nding is similar to an earlier report on strains from Taiwan [14]. This limits the usefulness of ribotyping in epidemiological investigations of S. sonnei.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The present study showed the poor discriminatory power of ribotyping for S. sonnei isolates. This ®nding is similar to an earlier report on strains from Taiwan [14]. This limits the usefulness of ribotyping in epidemiological investigations of S. sonnei.…”
Section: Discussionsupporting
confidence: 88%
“…Recently, approaches at the DNA level have been used to discriminate between bacterial isolates. Plasmid pro®le analysis [9,10], ribotyping [11,12] and pulsed-®eld gel electrophoresis (PFGE) [13,14] have proved to be useful in discriminating isolates of Shigella spp.…”
Section: Introductionmentioning
confidence: 99%
“…The S. sonnei isolates were characterized by preparing total genomic DNA in agarose plugs and carrying out pulsed-field gel electrophoresis (PFGE) (1,7). After growth overnight in Trypticase soy broth (Difco Laboratories, Detroit, Mich.), 2 ml of each culture was washed in cell suspension buffer and resuspended in 0.5 ml of the same buffer.…”
Section: Methodsmentioning
confidence: 99%
“…DNA genotyping methods have been increasingly used for bacterial characterization. The most commonly used techniques remain analysis by restriction fragment length polymorphism [2], single-stranded conformational polymorphism [3], randomly ampli¢ed polymorphic DNA [4], pulse ¢eld electrophoresis [5] and ribotyping [6]. However, these techniques are laborious, expensive and not suitable for studying a large number of bacterial strains [7].…”
Section: Introductionmentioning
confidence: 99%